The populist radical right in 21st-century Portugal - Marchi, R. (Portugal since the 2008 economic crisis: Resilience and change, 2023)
With a certain delay, right-wing populism is on the rise in Portugal, following the Western trend. Since the 2019 general election and for the first time in Portuguese democracy, a populist party of the radical right, Chega (Enough), has entered the national parliament, thanks to the election of its leader André Ventura. Chega has grown rapidly in terms of the number of militants and its electoral performance over the past three years, going from a few hundred members to at least 25,000 and from a vote share of 1.3% in the 2019 general election to 7% in 2022 (and from one to 12 seats). Meanwhile, Ventura obtained 12% of the vote in the 2021 presidential election. In 2022, Chega was the third most important political force in parliament, behind the two historical mainstream governmental parties, the Partido Socialista (Socialist Party) and the Partido Social Democrata (Social Democrat Party). The chapter looks at the history of Chega and its leader from the beginning and analyses the political culture of the party’s rank and file. The analysis is based on a survey of 3,000 party members carried out in October 2021. The data presented reveal attitudes towards Portuguese national identity and democracy.